The Sumatran Tiger's Corridor in Agam, West Sumatra: An Initial Analysis of the Metrics Indices Landscape - Munawar, Kholis; Syartinilia; Datu Bahaduri, Laksmi (Media Konservasi, 2026)
Increased habitat pressure is indicated by high levels of human-tiger conflict (HTC). For Sumatran tigers to survive, structural corridor management is essential to managing the tiger metapopulation. Since 2016, Agam Regency has seen a sharp rise in HTC. This exploratory study aimed to understand variations in the corridor's forest cover and to evaluate the relationship between landscape metric indicators and fluctuations in HTC density. Agam's corridor is separated into 31 grids (3x3km). HTC information was gathered from earlier studies and web searches for incidents from 2000 to 2024. Tropical Forest Monitoring's landcover dataset was obtained through the use of a Google Earth Engine script. The LecoS plug-in is used to calculate landscape metric indices. For non-normally distributed data, the Spearman correlation statistic (95% CI) is employed. Before the HTC series in 2016, there was a twofold increase in deforestation, from 0.56% to 1.1% between 2010 and 2015. Nine landscape metrics, including forest area, forest proportion, NP, PD, GPA, LPI, PCI, and splitting index, exhibited a significant correlation with HTC density (p-value < 0.05). Around the corridor, high HTC density was associated with PD >10 patches km-2, LPI <44%, forest fraction <50.76%, and more disaggregated patches (PCI<9.79%). Since it may not be feasible to reduce HTC to zero incidents in the vicinity of human-dominated tiger habitats, expectations should be moderated, as lower HTC density occurs in wider landscape metric ranges. Improving PCI by aggregating patches and reducing NP while maintaining the remaining forest can potentially reduce HTC incidents and increase corridor function in tiger metapopulation management. The challenges are enormous, as  94% the corridor is in a non-protected area.